Structure and mechanical properties of nitride multilayer systems on the basis of high entropy alloys and transition metals of group VI - Nyemchenko, U. S.; Beresnev, V. M.; Sobol, O. V.; Lytovchenko, S. V.; Stolbovoy, V. A.; Novikov, V. Ju.; Meylekhov, A. A.; Postelnyk, A. A.; Kovaleva, M. G. (My University, 2016)
The influence of technological parameters of obtaining on the possibilities of structural engineering and mechanical properties of multilayer compositions of the layers of nitrides of high entropy alloy Ti-Zr-Nb-Ta-Hf and of transition metal (Group IV) nitrides has been analysed. It is shown that with the bias potential Ub lesser than -150 V was applied to the substrate during deposition, a two-phase state with the preferred orientation of the crystallites can be reached in multilayer coatings with the thickness of the layers of 50 nm. This leads to high hardness (up to 44 GPa) and to high adhesion strength (critical load up to 125 N) as well as to low wear (with a counterbody Al ₂O₃, and with steel Ac100Cr6). High-temperature annealing (700 ⁰C) of such coatings leads to enhanced texture as a result of atomic ordering, which is accompanied by increasing of hardness up to 59 GPa. The supply of bias potential exceeding 150 V, followed by a substantial mixing at the interphase boundary results in disorientation and improves dispersion of the crystallites, reduces hardness and wear resistance. High temperature annealing of such structures leads to reduction of their mechanical properties.

Проаналізовано вплив технологічних параметрів отримання на можливості структурної інженерії та механічні властивості багатошарових композицій з шарів нітридів високоентропійних сплавів Ti-Zr-Nb-Ta-Hf і нітридів перехідних металів VI групи. Показано, що при потенціалі зміщення Us менше -150 В, що подається на підкладку при осадженні, у багатошарових покриттях з товщиною шарів близько 50 нм можна досягти двофазного стану з переважною орієнтацією кристалітів, що обумовлює високу твердість (до 44 ГПа) і одночасно високу адгезійну міцність (критичне навантаження до 125 Н), а також низький знос (як з контртілом Al₂O₃, так і зі сталлю Ac100Cr6). Високотемпературний відпал (700 ⁰С) таких покриттів призводить до посилення текстури в результаті атомарного упорядкування, що супроводжується зростанням твердості до 59 ГПа. Подача потенціалу зміщення, що перевищує 150 В, супроводжується істотним перемішуванням на міжфазній межі, що призводить до розорієнтації і підвищення дисперсності кристалітів, зменшення твердості і зносостійкості. Високотемпературний відпал таких структур призводить до зниження механічних властивостей.
Структура і механічні властивості нітридних багатошарових систем на основі високоентропійних сплавів і перехідних металів VI групи
Keywords: nitride multi layer systems; high entropy alloys; transition metals; structural engineering; mechanical properties; wear resistance; структурна інженерія; твердість; зносостійкість; кристаліти; хімічні реакції